2020
DOI: 10.1109/jphot.2020.2974881
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Repetition Rate Adjustable SBS-Based Q-Switched Fiber Laser

Abstract: We experimentally demonstrated a novel repetition rate adjustable SBS-based Q-switched fiber laser. An inserted Fabry-Perot interferometer formed by two non-contact end faces of two FC/PC fiber connectors was inserted to help the system stabilize the random output of SBS-based Q-switching. By mechanically fine-tuning the length of the inserted Fabry-Perot interferometer, a linear and continuous repetition rate adjustment under a fixed pump power was achieved. This method paves a new way for the indirect contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These properties demonstrate that bismuthene has potential application for spintronics, designing and fabricating room-temperature nondissipative quantum computing devices, ultrafast pulse lasers, and so on. , Ultrashort pulse fiber lasers have also garnered tremendous interest from the researchers because of the compact design structure, low cost, high-efficiency of heat dissipation, and convenient operation. It has been widely applied to many field including materials microprocessing, medicine surgery, and optical fiber telecommunication systems. Huge numbers of materials, such as semiconductor saturable absorber mirrors, graphene, topological insulators, black phosphorus, transition metal dichalcogenides, noble metal nano materials, transition metal chalcogenides, and so on, have been reported to be applied to the generation of ultrashort pulse laser because of its saturable absorption. In addition, broadband, GHz high repetition rate, tunable, and switchable multiwavelength ultrafast fiber lasers also attract further attention because of its potential application in many fields. Moreover, few-layer bismuthene also can be used in the field of ultrafast photonics and nonlinear optics to achieve ultrashort pulse laser. In 2018, Lu et al reported an ultrafast fiber laser with 652-fs optical pulse duration at a center wavelength of 1559.18 nm .…”
Section: Introductionmentioning
confidence: 99%
“…These properties demonstrate that bismuthene has potential application for spintronics, designing and fabricating room-temperature nondissipative quantum computing devices, ultrafast pulse lasers, and so on. , Ultrashort pulse fiber lasers have also garnered tremendous interest from the researchers because of the compact design structure, low cost, high-efficiency of heat dissipation, and convenient operation. It has been widely applied to many field including materials microprocessing, medicine surgery, and optical fiber telecommunication systems. Huge numbers of materials, such as semiconductor saturable absorber mirrors, graphene, topological insulators, black phosphorus, transition metal dichalcogenides, noble metal nano materials, transition metal chalcogenides, and so on, have been reported to be applied to the generation of ultrashort pulse laser because of its saturable absorption. In addition, broadband, GHz high repetition rate, tunable, and switchable multiwavelength ultrafast fiber lasers also attract further attention because of its potential application in many fields. Moreover, few-layer bismuthene also can be used in the field of ultrafast photonics and nonlinear optics to achieve ultrashort pulse laser. In 2018, Lu et al reported an ultrafast fiber laser with 652-fs optical pulse duration at a center wavelength of 1559.18 nm .…”
Section: Introductionmentioning
confidence: 99%